Integration of the social development and management programs of mining companies into the comprehensive sustainable development planning the case of Homonhon Island, Guiuan, Eastern Samar - Teng-Almocera, Siela B.; Jago-on, Karen Ann B. (Quezon City School of Urban and Regional Planning, University of the Philippines Diliman, 2025)
This study explores the integration of Social Development and Management Programs (SDMP) of mining companies into local development plans, focusing on Homonhon Island, Guiuan, Eastern Samar. The Philippines, rich in mineral resources, faces sustainability challenges in its mining sector. The Mining Act of 1995 mandates responsible mining practices, including the development of SDMPs to benefit hast communities. This research examines the planning, implementation, and monitoring of SDMPs by mining companies on Homonhon Island and their integration into the Comprehensive Sustainable Development Plan (CSDP) of Homonhon Island and the Comprehensive Development Plan (CDP) of Guiuan.
The study employs a qualitative approach, including secondary data analysis. thematic analysis, surveys, and focus group discussions. Data was collected from key informant interviews, focus group discussions with mining companies and barangay officials, and surveys of residents from five host mining barangays.
The findings reveal that SDMPs have significantly improved socioeconomic conditions in host communities, addressing education, health, infrastructure, and cultural values. However, issues like equity, transparency, and sustainability need improvement The study highlights the importance of aligning SDMPs with local development plans to
ensure their sustainability and long-term socioeconomic benefits. In addition, the creation of the CSDP has initiated opportunities for integration, fostering communication and collaboration among stakeholders.
The research concludes that integrating SDMPs into local development plans is feasible and beneficial for the socioeconomic development and sustained growth of Homonhon Island. Recommendations include regular joint planning sessions, capacity-building programs, the strategic allocation of funds, and robust monitoring systems. The study underscores the need for a formal mechanism for information exchange and participation in planning activities to minimize the duplication of efforts and maximize resource use.
Thesis
Keywords: Mines and mineral resources -- Philippines -- Guiuan (Eastern Samar).; Mines and mineral resources -- Philippines -- Homonhon Island (Eastern Samar).